Evidence of vertical transmission of ostreid herpesvirus 1 in the Portuguese oyster Crassostrea angulata - Sanmartin, Monserrat Lopez (2017)
In order to determine if ostreid herpesvirus 1 (OsHV-1) can be vertically transmitted, 9 full-sib families of the Portuguese oyster Crassostrea angulata were produced using a factorial mating design with 3 males and 3 females. The parents were survivors from an OsHV-1 mortality outbreak. OsHV-1 DNA was not detected by conventional PCR in the mantle of parents, gametes or 3 day-old larvae. However, viral DNA was detected by real-time PCR in all gametes and larvae samples. These results show that C. angulata that have survived an OsHV-1 mortality outbreak can carry the virus and vertically transmit it to their offspring. (C) 2016 Elsevier Inc. All rights reserved.